Analisa Keekonomian Sistem dengan Optimalisasi Pembangkit EBT dan Pertimbangan Biaya Eksternalitas - Sadmoko H Pambudi (Prosiding SISFOTEK, 2020)
Power plant development planning challenged by several targets such as increasing renewable energy (RE), reducing greenhouse gas (GHG) emissions and commitment to environmental sustainability while still considering economic principles. Utilization of RE still not optimal due to ability to compete economically with fossil fuel plants. This underlies the need for an analysis of the costs of externalities as compensation for fossil energy use on public health and the environment using the amount of SO2 and Nox. This study use least cost optimization model called Balmorel to modelling optimal alternatives on electricity demand and comparison of investment costs in several scenarios, including the target percentage of RE utilization in the National Energy General Plan (RUEN), The commitment to reduce GHG emissions, and scenarios when externality costs applied on fossil fuels. The result show that the application of externality costs will provide highest percentage of NRE utilization of 60% with an electricity tariff of 7.25 US cents / kWh, exceeding the target of NRE utilization in RUEN of 40.6% in 2040, and being able to fulfill the GHG emission reduction commitment on Nationally Determined Contribution (NDC) in 2030 with 214 million tons of CO2 emissions (60.1% lower than the NDC CM1 target and 58% lower than CM2).